Insecurity and Self-Acceptance Portrayed in Samsung Galaxy A8 Advertisement “Lets You Be You”: A Multimodal Analysis - Stefanus Fernando (Institute of Research and Community Outreach - Petra Christian University, 2019)
This study analyzed the issue of insecurity and self-acceptance portrayed in Samsung Galaxy A8 advertisement entitled “Lets You Be You”. The main theory for this study is the theory of multimodal discourse analysis by Paltridge (2012) and the theory of body language by Pease (2004) as the supporting theory. Qualitative approach is applied because this study involves the interpretation of both verbal and nonverbal data. The findings showed how the issue of insecurity is reflected through the reaction of the participants in the video before and after receiving a compliment. Furthermore, the construction of the changing process from insecurity to self-acceptance can be seen from the genuine reaction of the compliment, as well as the change of facial expression throughout the video. Key words: Insecurity, Self-acceptance, Multimodal Discourse Analysis, Advertisement, Samsung